Environmental Chemistry and Recent Pollution Control Approaches - Saldarriaga-Noreña, Hugo; Alfonso Murillo-Tovar, Mario; Farooq, Robina; Dongre, Rajendra; Riaz, Sara (IntechOpen, 2019)
In recent years, there have been significant advances in the techniques of sampling and analysis, which has allowed the more accurate recording of environmental levels of many substances present in the environment. At the same time, processes for the remediation of contaminated matrices have evolved, through the application and/or combination of biological, physical, and chemical procedures.The purpose of this book is to present new studies aimed at determining levels of environmental pollution in various parts of the world. It also shows new alternatives for the remediation of contaminated matrices.